Insights into biochar supported atomically dispersed cobalt as an efficient peroxymonosulfate activator for sulfamethoxazole degradation: robust performance, ROS and surface electron-transfer pathways. Issue 9 (22nd August 2022) - Gu, Chunyao; Zhang, Yaqin; He, Peng; Zhu, Jianyu; Gan, Min
Abstract : Atomically dispersed catalysts, owing to utmost atomic utilization, have gained widespread interest in SR-AOPs, and yet, tremendous challenges remain in the facile synthesis of efficient, robust, and sustainable catalysts for persulfate activation. Abstract : Atomically dispersed catalysts, owing to their utmost atomic utilization, have gained widespread interest in sulfate radical-based advanced oxidation processes, and yet, tremendous challenges remain in the facile synthesis of efficient, robust, and sustainable catalysts for persulfate activation. Here, we adopted a ligand-mediated method, using inexpensive biochar as a support, to prepare an atomically dispersed cobalt catalyst (0.5-Co–N@BC). 0.5-Co–N@BC displayed outstanding catalytic performance with 1.267 min −1 turnover frequency on peroxymonosulfate (PMS) activation for sulfamethoxazole (SMX) degradation. The 0.5-Co–N@BC/PMS system demonstrated promising results in recycling, different initial pH values (4.1–10.0) and water sources, and possessed high resistance to environmental interference. Quenching experiments and electron paramagnetic resonance confirmed the existence of reactive oxygen species (including sulfate radical and singlet oxygen), and electrochemical tests revealed that the surface electron-transfer pathway was also involved in the SMX degradation. The activation pathways were determined with the adsorption of SMX by pyrrolic N on the 0.5-Co–N@BC surface and the adsorption and activation of PMS by octahedral cobalt. This study provided new insights into the activation pathway and mechanism of biochar-supported atomically dispersed cobalt catalyzed PMS activation and its potential application in the future.